Long-term landscape changes in vegetation structure: fire management in the wetlands of KwaMbonambi, South Africa - Luvuno, LB; Kotze, DC; Kirkman, KP (African journal of aquatic science, 2016)
In wetlands the effects of fire on vegetation dynamics are somewhat uncertain. A change detection analysis in the herbaceous wetlands of KwaMbonambi, South Africa, which were subject to frequent fires, revealed that in 1937 the study area comprised grassland (69%), herbaceous wetland (25%), indigenous swamp forest (4%) and tree plantations (1%). However, by 1970, tree plantations occupied 78% of the landscape and grasslands and herbaceous wetlands had declined to 9% and 6%, respectively, whereas indigenous swamp forest had increased to 6%. By 2009 tree plantations had been removed from the wetland areas. Despite this opportunity for herbaceous wetlands to recover their historical extent, they decreased to only 2%, mostly changing to indigenous swamp forest or to an herbaceous/fern (Stenochlaena tenuifolia)/woodland mosaic. Fire records showed suppression of fire to be an important contributing factor, particularly in wetlands that had been disturbed by tree plantations, although subsequently removed. A pilot burning experiment revealed that S. tenuifolia did not inhibit fire. It is therefore practicable to increase fire frequency to prevent the mosaic developing into forest. A conceptual model of the influence of fire regime on wetland vegetation type is presented and priorities for further research on wetlands and fire are recommended.